2002
DOI: 10.4049/jimmunol.168.12.6323
|View full text |Cite
|
Sign up to set email alerts
|

A Founder Mutation in Artemis, an SNM1-Like Protein, Causes SCID in Athabascan-Speaking Native Americans

Abstract: Athabascan SCID (SCIDA) is an autosomal recessive disorder found among Athabascan-speaking Native Americans and is manifested by the absence of both T and B cells (T−B−NK+ SCID). We previously mapped the SCIDA gene to a 6.5-cM interval on chromosome 10p. SCIDA fibroblasts were found to have defective coding joint and reduced, but precise signal joint formation during V(D)J recombination. After excluding potential candidate genes, we conducted a combined positional candidate and positional cloning approach lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 44 publications
3
112
0
2
Order By: Relevance
“…We previously demonstrated the absence of V(D)J recombination-derived coding joint with normal signal joint formation in patients with defective Artemis (SCIDA). 8,13 In contrast, this mutation in RAG-1 cannot facilitate signal or coding joint formation, indicating that the R776W RAG-1 either fails to incise DNA or completely blocks subsequent recombination steps in vivo. It appears that this single amino-acid replacement in RAG-1 (R776W) results in a nearly complete failure of V(D)J recombination and the subsequent T and B cell deficiencies and disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously demonstrated the absence of V(D)J recombination-derived coding joint with normal signal joint formation in patients with defective Artemis (SCIDA). 8,13 In contrast, this mutation in RAG-1 cannot facilitate signal or coding joint formation, indicating that the R776W RAG-1 either fails to incise DNA or completely blocks subsequent recombination steps in vivo. It appears that this single amino-acid replacement in RAG-1 (R776W) results in a nearly complete failure of V(D)J recombination and the subsequent T and B cell deficiencies and disease.…”
Section: Discussionmentioning
confidence: 98%
“…Our original linkage study mapped the SCIDA genetic defect to chromosome 10p 13 and we subsequently identified a founder mutation in Artemis as the cause of SCIDA in Navajo and Apache Native Americans. 8,14 Surprisingly, this Artemis mutation was not found in the three T À B À NK þ SCID children from two related kindreds of Dine Indians in the Canadian Northwest Territories, a linguistically and genetically related people.…”
Section: Introductionmentioning
confidence: 93%
“…Human SCID with increased IR sensitivity has thus far been described in patients with null mutations in the Artemis gene and is characterized by a complete absence of T and B lymphocytes [16][17][18][19]. We herein report the occurrence of a RS-SCID, characterized by a virtual absence of B lymphocytes and a residual number of T cells, associated with microcephaly in two siblings as a consequence of mutations in the V(D)J/NHEJ factor Lig4-encoding gene.…”
Section: Discussionmentioning
confidence: 99%
“…The second group is additionally characterized by increased cellular sensitivity to ionizing radiations (IR), which points to a general DNA repair deficiency [15]. This radiosensitive SCID (RS-SCID) is caused by null mutations in the V(D)J/NHEJ factor Artemis [16][17][18][19]. Given the embryonic lethality of both Lig4 and Xrcc4 KO mice one does not expect to identify patients with complete loss of function in either gene.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the remaining patients show hypersensitivity to ionizing radiation, because the V(D)J recombination deficiency results from a defect in NHEJ. The majority of these patients have mutations in Artemis (Moshous et al, 2001;Li et al, 2002;Kobayashi et al, 2003;Noordzij et al, 2003). The clinical phenotype of RAG1, RAG2 and Artemis-deficient patients is similar and can be mimicked in mice (Table 1).…”
Section: Intersection Of Nhej With Other Cellular Processesmentioning
confidence: 99%